Spatial analysis of sub-regional variation in Southern US English. Issue 2 (8th October 2021) - Jones, Jonathan A.; Renwick, Margaret E. L.
Abstract: This project uses GIS mapping to analyze spatial trends in spoken language, testing how features identified as part of the "Southern dialect" by the Atlas of North American English ( ANAE ; Labov et al., 2006 ) are used in the Digital Archive of Southern Speech (DASS; Kretzschmar et al., 2013 ). We analyze vowel mergers, diphthongization, monophthongization, fronting, and several consonantal features. Rather than drawing isoglosses, we use local spatial autocorrelation analysis to reveal subregional patterning in the data. We present a series of maps illustrating the realization of Southern speech features as enumerated by ANAE . We find little evidence for ANAE 's Inland South region based on acoustics, and while some areas surveyed in DASS align well with the portrayal of Southern speech presented by ANAE, others do not.